Comparison of Myocardial Mechanical Metrics in Electromechanical Model vs. Fluid-Electromechanical Model - Ahmad Bakir, Azam; Mohamed Mokhtarudin, Mohd Jamil (International Journal of Integrated Engineering, 2025)
The development of multiphysics heart model has grown tremendously over the past decade. In this paper, we compare two multiphysics approaches: electromechanics and fluid-electromechanics, in simulating left ventricular mechanics and the output of mechanical metrics. Cardiac electromechanical (EM) model refers to the approach of simulating heart mechanical deformation, triggered by cardiac action potential, while the generated ventricular pressure is determined by a penalty function and applied uniformly across the endocardium. Fluid-electromechanics (Fluid-EM) approach relies on similar action potential wave to trigger mechanical deformation but the ventricular pressure is determined by solving the Navier-Stokes equations within the ventricular cavity. Thus, Fluid-EM is more accurate as it models the blood-ventricular interaction, producing more realistic loading on the endocardium and enabling analysis of blood flow dynamics. Due to its complexity, the Fluid-EM approach is more computationally demanding than the EM approach. We assessed several mechanical metrics within the ventricle namely stresses and strains to assess regional differences in the heart by implementing both approach in a heart geometry extracted from a healthy patient. Differences in the mechanical metrics were noted indicating both models were loaded differently due to differences in modelling the blood. This suggests that in greater differences can be expected should there be more regional differences in the myocardium such as in infarct cases.